Sucralose consumption ameliorates high-fat diet-induced glucose intolerance and liver weight gain in mice - Pino-Seguel, Pamela; Moya, Omara; Borquez, Juan Carlos; Pino-de la Fuente, Francisco; Díaz-Castro, Francisco; Donoso-Barraza, Camila; Llanos, Miguel; Troncoso, Rodrigo; Bravo-Sagua, Roberto (Frontiers in Nutrition, 2022)
Sucralose is one of the most widely used artificial sweeteners used by the food industry to reduce the calorie density of their products. Although broadly regarded as innocuous, studies show contrasting results depending on whether the research subjects are lean or overweight. In this study, we studied the effect of sucralose consumption on glucose homeostasis in a model of obesity. Male C57BL/6J mice were fed ad libitum with control or a high-fat diet (HFD) and drank either water or sucralose (0.1 mg/mL) for 8 weeks. To characterize the ensuing metabolic changes, we evaluated weight gain, glucose and pyruvate tolerance, and physical performance. Also, we assessed markers of steatosis and mitochondrial mass and function in the liver. Our results show that sucralose reduced weight gain, glucose, and pyruvate intolerance, and prevented the decrease in physical performance of HFD-fed mice. In the liver, sucralose also had a protective effect, preventing the increase in AST, decreasing the relative liver weight, and averting the decrease in mitochondrial mass. Altogether, our results indicate that in the context of an obesogenic diet, sucralose has a beneficial effect at the organismal and hepatic levels.